Answer:
x = 1
Explanation:
Simplifying
2x + -7 = 5x + -10
Reorder the terms:
-7 + 2x = 5x + -10
Reorder the terms:
-7 + 2x = -10 + 5x
Solving
-7 + 2x = -10 + 5x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-5x' to each side of the equation.
-7 + 2x + -5x = -10 + 5x + -5x
Combine like terms: 2x + -5x = -3x
-7 + -3x = -10 + 5x + -5x
Combine like terms: 5x + -5x = 0
-7 + -3x = -10 + 0
-7 + -3x = -10
Add '7' to each side of the equation.
-7 + 7 + -3x = -10 + 7
Combine like terms: -7 + 7 = 0
0 + -3x = -10 + 7
-3x = -10 + 7
Combine like terms: -10 + 7 = -3
-3x = -3
Divide each side by '-3'.
x = 1
Simplifying
x = 1